Integrative Approach to COVID-19: An Indian Facebook Recipe for Mental Health. Issue 3 (July 2021) - Anand, Akshay; Tyagi, Rahul; Khosla, Radhika; Bali, Parul; Rain, Manjari; Maity, Kalyan; Verma, Prashant; Gupta, Sheetal J; Nadholta, Pooja; Kaur, Navneet; Sharma, Kiran; Tripathi, Satyam; et al.
Background: The COVID-19 pandemic has given the world a big blow and has forced the entire world to develop a new thought process. To cope with the stress of lockdown, it was important for people to indulge in educational and health activities to save them from the threats being caused by the news and social media. Summary: A Facebook page named Yoga scholars Post Graduate Institute of Medical Education and Research (PGIMER) was created where three sessions were held per day for 225 days regularly. This activity resulted in people adopting an integrative approach towards alternative medicine. Key message: This also made possible a trial of Ashwagandha for COVID-19 treatment by the Ayurveda, Yoga, Naturopathy, Unani, Siddha and Homeopathy (AYUSH) ministry.